The Importance of Industry Links in Merger Waves - AHERN, KENNETH R.; HARFORD, JARRAD (Journal of Finance, 2014)
ABSTRACT We represent the economy as a network of industries connected through customer and supplier trade flows. Using this network topology, we find that stronger product market connections lead to a greater incidence of cross‐industry mergers. Furthermore, mergers propagate in waves across the network through customer‐supplier links. Merger activity transmits to close industries quickly and to distant industries with a delay. Finally, economy‐wide merger waves are driven by merger activity in industries that are centrally located in the product market network. Overall, we show that the network of real economic transactions helps to explain the formation and propagation of merger waves.